Upaya Guru Pendidikan Agama Islam dalam Meningkatkan Kemampuan Baca Tulis Al-Qur’an Siswa Kelas IV SD Nurul Iman Bontang Tahun Pembelajaran 2022/2023 - Nurhaliza, Trisna (Sekolah Tinggi Ilmu Tarbiyah Syamsul Ma'arif Bontang, 2025)
This article examines the efforts of Islamic Religious Education (IRE) teachers in enhancing the Qur'anic reading and writing skills of fourth-grade students at SD Nurul Iman Bontang. The study aims to identify the specific strategies employed by IRE teachers to improve these skills and to analyze how these strategies contribute to students' proficiency in reading and writing the Qur'an. The research adopts a descriptive qualitative approach, utilizing data collected through observation, interviews, and documentation. The findings reveal that students demonstrate significant proficiency in reading and writing the Qur'an. The instruction of Qur'anic reading and writing is integrated into the Islamic Religious Education (IRE) curriculum, allowing students' progress in these skills to be reflected in their subject grades. The study concludes that the efforts of IRE teachers involve a range of practices, including cultivating the habit of Qur'anic recitation with proper tajwid, guiding students in accurate recitation, providing exercises on reading and writing Qur'anic verses, assigning tasks to write verses and their meanings, implementing group study systems, utilizing Qur'anic manuscripts (mushafs), conducting prayer practice sessions in mosques, reinforcing learning through repetition, and delivering material through lectures, songs, or clapping techniques. These strategies collectively contribute to enhancing students' Qur'anic reading and writing abilities at SD Nurul Iman Bontang.